The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jcp.27065
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6/YAP1/β‐catenin signaling is involved in intervertebral disc degeneration

Abstract: Yes‐associated protein 1 (YAP1) is a transcriptional coactivator and negative regulator of the Hippo pathway. It regulates diverse cellular processes, such as cell proliferation, contact inhibition, and tissue size. However, the role of YAP1 in intervertebral disc degeneration (IDD) remains elusive. Here, we demonstrated that YAP1 was activated by Interleukin 6 (IL‐6) through tyrosine phosphorylation in nucleus pulposus cells (NP cells). Overexpression of YAP1 decreased Sox‐9, Col‐II, aggrecan expression, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…IL-6 rs1800795 and rs1800797 polymorphisms, located within regulatory regions, could be part of RNAbinding protein site and could be involved in RNAbinding which is protein-mediated. Previous studies showed that IL-6 significantly induced disc degeneration by activating STAT3 and β-catenin signaling pathways [30,34]. It seems to indicate that IL-6 might act synergistically with other genetic factors contributing to the risk of disc degeneration.…”
Section: Discussionmentioning
confidence: 94%
“…IL-6 rs1800795 and rs1800797 polymorphisms, located within regulatory regions, could be part of RNAbinding protein site and could be involved in RNAbinding which is protein-mediated. Previous studies showed that IL-6 significantly induced disc degeneration by activating STAT3 and β-catenin signaling pathways [30,34]. It seems to indicate that IL-6 might act synergistically with other genetic factors contributing to the risk of disc degeneration.…”
Section: Discussionmentioning
confidence: 94%
“…One study in dogs showed an upregulation in the gene expression of IL-8 and downregulation in the gene expression of IL-6 during IVDD (11). Increased levels of IL-6 and IL-8 in IVD in humans correlate with degeneration and inflammation within the IVD (36,(43)(44)(45)(46). Aside from its catabolic effects on NP cells, IL-6 is also involved in the development of pain during the course of IVDD (47).…”
Section: Discussionmentioning
confidence: 99%
“…Inside the nucleus, YAP/TAZ has been reported to act as a transcriptional coactivator for a multitude of proteins. YAP/TAZ interacts with additional DNA‐binding coactivators like TEADs, tumor protein p73, SMADs, FOXO proteins, T‐box transcription factor 5, RUNT‐related transcription factors (RUNX1, 2), and some other factors to regulate a diverse range of target gene expressions and thus diverse cellular responses (Boopathy & Hong, ; Chen et al, ; Fallahi et al, ). TEAD is one of the most studied transcriptional regulators that associate with YAP/TAZ.…”
Section: Overview Of the Hippo Signaling Networkmentioning
confidence: 99%